DNA transfer between evidence bags: is it a means for incidental contamination of items?. Issue 3 (4th May 2021) - Mercer, Claire; Abarno, Damien; Hearnden, Phillippa; Linacre, Adrian
ABSTRACT: With the increasing sensitivity of DNA profiling systems, the opportunity to detect incidental DNA transferred between evidential items has increased. Evidence bags are assumed to be DNA transfer vectors which can cause an inadvertent transfer of DNA between items, yet little has been studied to indicate the extent of this transfer. This study aimed to provide insight into the levels of DNA accumulating on evidence bags through exhibit handling and storage. Casework exhibit bags were sampled during storage and mock exhibit bags were sampled after replicating exhibit handling protocols. DNA concentrations recovered from casework exhibit packages were highly variable and produced profiles containing up to at least seven contributors. The DNA concentration and profile complexity was higher in samples taken from packages after exhibit examination. It was observed that DNA from the exhibit can be transferred to the exterior of the bag during the process of packaging and un-packing the item. Profile complexity from mock exhibit packages increased with time spent in the exhibit storeroom. With the introduction of highly sensitive DNA profiling systems, procedures involving the handling, transport and storage of exhibits should be assessed to ensure that best-practice contamination minimization procedures are being utilized.